Reduced levels of nitrated α-synuclein in the protective effect of harpagoside on rotenone-induced cellular models of Parkinson’s disease - Lang, Juan; Xiong, Zhongkui (Frontiers in Cell and Developmental Biology, 2025)
IntroductionParkinson’s disease (PD), ranking as the second most common neurodegenerative disorders following Alzheimer’s disease, involves the progressive accumulation of misfolded proteins in affected neural tissues. This pathological process appears linked to overproduction of reactive oxygen species (ROS) and reactive nitrogen species (RNS). Significantly, more than 30% of proteins aggregated in Lewy bodies exhibit post-translational modifications, particularly RNS-mediated nitration and S-nitrosylation. Experimental evidence suggests that α-synuclein nitration promotes its misfolding and neurotoxic effects in PD models.MethodsTo model PD pathology, rotenone was applied to induce cellular damage in Neuro-2A (N2A) cells and BV-2 microglial cells. Three iridoid constituents from Scrophularia ningpoensis Hemsl, harpagoside, acetylharpagide, and haragide, were investigated for their neuroprotective potential against rotenone-induced cytotoxicity, with catalpol serving as reference compound. Cell viability was assessed using the CCK-8 assay, nitric oxide (NO) levels were measured via the nitroso assay, nitric oxide synthase (NOS) activity was determined by enzyme-linked immunosorbent assay (ELISA), and nitrated α-synuclein expression was evaluated through immunocytochemistry.ResultsOur studies revealed that both acetylharpagide and harpagoside demonstrated substantial cytoprotective effects on rotenone-treated N2A cells. Further investigation focusing on harpagoside showed its ability to suppress NO generation and inhibit α-synuclein nitration.DiscussionDetailed pathway analysis indicated that harpagoside’s protective actions involved regulation of the nuclear factor-κB (NF-κB)/NOS/NO/α-synuclein nitration signaling cascade.